Model Pembelajaran berbasis E-Learning di Sekolah - Suryanti, Eny Wahyu; Bariyah, Khoirotul (FKIP Universitas Wisnuwardhana, 2021)
The learning process is a series of interactions between teachers and students to achieve predetermined learning goals or in other words learning is a form of learning process and maturation of students. During the COVID-19 pandemic, the government adopted a policy to implement online learning as an effort to prevent the spread of the COVID-19 virus. Online learning activities require creative and innovative learning models so that students can carry out learning activities effectively. With e-learning, learning materials are also delivered in detail and help students make it easier to understand learning materials. The purpose of this study is to determine the e-learning learning model in schools. This type of research is a descriptive qualitative approach with data obtained from observations, interviews, and documentation. The results showed that the e-learning-based learning model in schools had two systems in delivering learning materials to students, namely; 1) Synchronous (directly), the teacher provides learning materials and students can directly listen to them, and 2) A-Synchronous (indirectly), messages or learning materials are not directly conveyed to students but recorded first.